Comparing Green Economy in Iran with OECD Asian Countries by Applying TOPSIS and GI Method - Iman Ajripour; Rosa Alamian (Theory, Methodology, Practice, 2021)
In this study, we tried to calculate Iran’s green growth index and compare it with four selected OECD countries in the continent of Asia, Turkey, Japan, Korea, and Israel in 2015 by applying the Green Index, and Technique for Order of Preference by Similarity to Ideal Solution. Our research provides a new methodology to rank different countries based on green growth indicators. Applying both methods, Iran ranked fourth among the selected countries. Iran, in comparison to Turkey, Japan, and Korea, is behind in developing sustainability and green economy indices.